2016
DOI: 10.1136/annrheumdis-2015-208690
|View full text |Cite
|
Sign up to set email alerts
|

EULAR recommendations for the management of familial Mediterranean fever

Abstract: Familial Mediterranean fever (FMF) is the most common monogenic autoinflammatory disease, but many rheumatologists are not well acquainted with its management. The objective of this report is to produce evidence-based recommendations to guide rheumatologists and other health professionals in the treatment and follow-up of patients with FMF. A multidisciplinary panel, including rheumatologists, internists, paediatricians, a nurse, a methodologist and a patient representative, was assembled. Panellists came from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
385
0
74

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 454 publications
(461 citation statements)
references
References 68 publications
2
385
0
74
Order By: Relevance
“…Secondary amyloidosis appearing during the course of FMF was also a leading cause of resistance to colchicine, exclusively observed in the adult population. Physician’s assessment of resistance to colchicine treatment was in accordance with the definition of the French Israeli consortium, “six or more typical attacks in a year or three in 4–6 months with an elevated acute phase response between attacks,” and with the new EULAR recommendations, at least 1 attack/month in a 6-month period with full adherence to colchicine treatment [4, 13]. Another finding is that a number of patients, especially children, received doses of colchicine higher than that recommended and experienced digestive symptoms of intolerance, which could be considered not strictly synonymous with resistance to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary amyloidosis appearing during the course of FMF was also a leading cause of resistance to colchicine, exclusively observed in the adult population. Physician’s assessment of resistance to colchicine treatment was in accordance with the definition of the French Israeli consortium, “six or more typical attacks in a year or three in 4–6 months with an elevated acute phase response between attacks,” and with the new EULAR recommendations, at least 1 attack/month in a 6-month period with full adherence to colchicine treatment [4, 13]. Another finding is that a number of patients, especially children, received doses of colchicine higher than that recommended and experienced digestive symptoms of intolerance, which could be considered not strictly synonymous with resistance to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, paediatric patients received higher doses than adults and had more side effects but were more fully adherent than adults (48% vs 22%). The international recommendations distinguish low adherence from resistance to colchicine treatment [4, 13], but the practical way to improve the management of this critical issue needs to be determined. New findings have shown that psychological “stress” is sensed by the innate immune system in the brain via the ATP/P2X7R-NLRP3 inflammasome cascade; reversing the activation of this pathway in mice blocked the release of IL-1β (1–3 days after infusion) and produced antidepressant and anxiolytic behavioural effects in non-stressed mice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the international collaboration of experienced experts from different countries, the European League Against Rheumatism (EULAR) recommendation set for the management of FMF has been published supported by the best available evidence (17). These recommendations are presented in Table 2.…”
Section: Treatmentmentioning
confidence: 99%
“…If the patient lacks clinical manifestations or subclinical inflammation, genetic diagnosis is not a precise indication to start treatment; however, these patients should be followed-up closely for clinical symptoms or signs of subclinical inflammation (17). In countries where amyloidosis has high frequency, the physician may consider treatment in these patients especially when the patient has homozygous M694V mutation, which is more frequently associated with the development of amyloidosis (9, 21, 7177).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation